How Work Stress and Employee Well-Being Shape Turnover Intention: Evidence from the Mediating Role of Employee Engagement - Evi Dwi Meilani; Irmawati Irmawati (Yayasan Riset dan Pengembangan Intelektual, 2025)
This investigation interrogates the ramifications of occupational strain and employee flourishing on the proclivity toward workforce attrition, concurrently examining the intercessory function of workforce engagement. Employing a sample of 103 participants, data were interrogated via SmartPLS analytics. Empirical evidence evinces that both occupational strain and employee flourishing exert substantive impacts on workforce engagement. Notably, employee flourishing demonstrably attenuates attrition proclivity, whereas occupational strain exacerbates it. Contrarily, workforce engagement does not manifest a statistically meaningful influence on attrition tendencies. Mediation analyses further corroborate that engagement fails to function as a conduit between either occupational strain or employee flourishing and attrition inclination. These insights insinuate that engagement alone is not a determinative mechanism in mitigating attrition, whereas employee flourishing constitutes a more potent determinant of employees’ intent to remain embedded within organizational structures.